Biodegradation of malathion and chlorpyrifos by some microorganisms isolated from agricultural drainage water in Egypt - Ayman Y. I. Ewida; Marwa E. El-Sesy; Eslam I. El-Aswar; Elsayed E. ElSayed (Water Science, 2023)
ABSTRACTMalathion and chlorpyrifos are pesticides used excessively for agricultural purposes in Egypt to fight insects. The presence of such toxic compounds in watercourses exhibits harmful threats to the environment. The technology of bio-removal (or biodegradation) is nowadays the alternate method for environmental curing. The present study aimed to isolate and identify microbial strains (fungi and bacteria) with strong capabilities of biodegrading such pesticides, and to evaluate their abilities to uptake both pesticides at the same time. Agricultural drainage water samples were collected from four different drains in Egypt, named; El-Rahawi drain, Giza Governorate; Sabal drain, Minufiya Governorate; Ketshiner drain, Kafr El-Shiekh Governorate and Genag drain, Gharbiya Governorate. Water quality studies were carried out for water samples including organophosphorus (OP) pesticide contamination using Gas Chromatography-Mass Spectrometry (GC-MS). Malathion and chlorpyrifos was detected in slightly high concentration in Genag drain. So, Genag drainage water was used as enrichment to isolate the microorganisms having pesticide-biodegrading abilities. A total of four fungal and two bacterial strains were isolated, all of which showed a high ability to biodegrade one or both of the pesticides. The identification of the fungal isolates was carried out by 18S rRNA sequence analysis as Aspergillus fumigatus, Aspergillus niger, Penicillium chrysogenum and Aspergillus flavus. The bacterial isolates were identified as Acinetobacter boumnnii and Pseudomonas putida using 16S rRNA sequence analysis. The results of the biodegradation – capabilities experiments indicated the promising efficiency of A. niger, P. chrysogenum and P. putida where they could remove 90.5%, 95% and 64.4% of malathion and 85.8%, 85% and 88.2% of chlorpyrifos, respectively. Also, they exhibited potential abilities in biodegrading both pesticides at once, so, we recommend the use of such microorganisms as tools for bioremediation of agricultural drainage water contaminated with pesticides.